It is safe to use transdermal glyceryl trinitrate to lower blood pressure in patients with acute ischaemic stroke with carotid stenosis. Issue 1 (19th March 2019) - Appleton, Jason P; Woodhouse, Lisa J; Belcher, Andrew; Bereczki, Daniel; Berge, Eivind; Caso, Valeria; Chang, Hui Meng; Christensen, Hanne K; Collins, Ronan; Gommans, John; Laska, Ann C; Ntaios, George; et al.
Abstract : Background: There is concern that blood pressure (BP) lowering in acute stroke may compromise cerebral perfusion and worsen outcome in the presence of carotid stenosis. We assessed the effect of glyceryl trinitrate (GTN) in patients with carotid stenosis using data from the Efficacy of Nitric Oxide in Stroke (ENOS) Trial. Methods: ENOS randomised 4011 patients with acute stroke and raised systolic BP (140–220 mm Hg) to transdermal GTN or no GTN within 48 hours of onset. Those on prestroke antihypertensives were also randomised to stop or continue their medication for 7 days. The primary outcome was the modified Rankin Scale (mRS) at day 90. Ipsilateral carotid stenosis was split: <30%; 30–<50%; 50–<70%; ≥70%. Data are ORs with 95% CIs adjusted for baseline prognostic factors. Results: 2023 (60.5%) ischaemic stroke participants had carotid imaging. As compared with <30%, ≥70% ipsilateral stenosis was associated with an unfavourable shift in mRS (worse outcome) at 90 days (OR 1.88, 95% CI 1.44 to 2.44, p<0.001). Those with ≥70% stenosis who received GTN versus no GTN had a favourable shift in mRS (OR 0.56, 95% CI 0.34 to 0.93, p=0.024). In those with 50–<70% stenosis, continuing versus stopping prestroke antihypertensives was associated with worse disability, mood, quality of life and cognition at 90 days. Clinical outcomes did not differ across bilateral stenosis groups. Conclusions: Following ischaemic stroke, severe ipsilateral carotid stenosis is associated with worse functional outcome at 90 days. GTN appears safe in ipsilateral or bilateral carotid stenosis, and might improve outcome in severe ipsilateral carotid stenosis.